Development of a Web-Based Nutritious Food Consumption Monitoring System - Megaria Purba; Liskedame Yanti Sipayung; Puteri Fajar Addini; Khairunisa; Julia Friska Sahputri (Universitas Budi Darma, 2026)
School meal programs require reliable records to determine whether meals are distributed and consumed as planned. At the observed school, consumption was recorded manually, creating risks of incomplete entries, delayed recapitulation, and difficulty retrieving historical data. This study developed a web-based nutritious food consumption monitoring system using the Waterfall model. Requirements were identified through observation, stakeholder interviews, and document review, then translated into Unified Modeling Language and database designs. The implemented modules cover role-based login, student records, food menus, daily consumption entries, and period-based reports. Functional verification used predefined black-box scenarios for authentication, data management, consumption recording, reporting, and logout. All seven primary scenarios produced the expected outputs, while two focused authentication cases correctly accepted valid credentials and rejected invalid credentials. These results show that the prototype satisfies the tested functional requirements and centralizes previously fragmented records. However, the 100% functional success rate applies only to the specified test cases and does not establish usability, performance, security, nutritional adequacy, or effectiveness in improving student health. Field deployment with representative users, measured task performance, security assessment, and validation of nutritional indicators is therefore required before operational adoption.